Peran Kepala Sekolah dalam Meningkatkan Inovasi dan Kreativitas Guru di Masa Pandemi di SD Muhammadiyah Bantul Kota - Hanif Kurniawan; Enung Hasanah (Jurnal Studi Guru dan Pembelajaran, 2021)
The aims of this research is to analyze role of Principal in improving innovation and creativity of teachers at SD Muhammadiyah Bantul Kota during the pandemic. This research uses descriptive research type from observation and interviews. The research sample was the principal, three teachers, the school committee, and two guardians and students. The role of the principal in improving teacher innovation and creativity in learning are (1) the principal as a role model; (2) supervision and guidance, (3) giving rewards and punishments, (4) involving teachers in training, (5) creating a pleasant working atmosphere, (6) giving freedom to innovate and be creative, (7) involving teachers in various competitions